PENGARUH KUALITAS AUDIT, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Leni Susanti; Silvia Margareta (JSMA, 2019)
Earnings management is manager’s choice to manipulate the company’s financial statements to several object’s benefit. Earnings management can decrease the credibility of financial statement that be used as base of decision making. The aim of this reseach is to find empirical evidence on the effects of audit quality, leverage, and firm’s size on earnings management. This research was conducted on manufacture companies on the Indonesia Stock Exchange from 2013-2017 and the samples of this research are 102 companies. The sampling technique was using purposive sampling method. Analysis method in this reseacrh was using multiple liniar regression. The results of this research indicate that either using De Angelo Model or Modified Jones Model audit quality, leverage, and firm’s size have a significant effect on earnings management simultantly. And partially by using De Angelo Model audit quality has a negative insignificant effect, leverage has a negative significant effect, and firm’s size has a positive insignificant effect on earnings management. While using Modified Jones Model partially audit quality has a negative significant effect, leverage has a negative significant effect, and firm’s size has insignificant effect on earnings management.